Guideline on management of the acute asthma attack in children by Italian Society of Pediatrics - Luciana Indinnimeo; Elena Chiappini; Michele Miraglia del Giudice; The Italian Panel for the management of acute asthma attack in children Roberto Bernardini (Italian Journal of Pediatrics, 2018)
Abstract Background Acute asthma attack is a frequent condition in children. It is one of the most common reasons for emergency department (ED) visit and hospitalization. Appropriate care is fundamental, considering both the high prevalence of asthma in children, and its life-threatening risks. Italian Society of Pediatrics recently issued a guideline on the management of acute asthma attack in children over age 2, in ambulatory and emergency department settings. Methods The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology was adopted. A literature search was performed using the Cochrane Library and Medline/PubMed databases, retrieving studies in English or Italian and including children over age 2 year. Results Inhaled ß2 agonists are the first line drugs for acute asthma attack in children. Ipratropium bromide should be added in moderate/severe attacks. Early use of systemic steroids is associated with reduced risk of ED visits and hospitalization. High doses of inhaled steroids should not replace systemic steroids. Aminophylline use should be avoided in mild/moderate attacks. Weak evidence supports its use in life-threatening attacks. Epinephrine should not be used in the treatment of acute asthma for its lower cost / benefit ratio, compared to β2 agonists. Intravenous magnesium solphate could be used in children with severe attacks and/or forced expiratory volume1 (FEV1) lower than 60% predicted, unresponsive to initial inhaled therapy. Heliox could be administered in life-threatening attacks. Leukotriene receptor antagonists are not recommended. Conclusions This Guideline is expected to be a useful resource in managing acute asthma attacks in children over age 2.